2020
DOI: 10.1186/s13017-020-00310-7
|View full text |Cite
|
Sign up to set email alerts
|

Which appendicitis scoring system is most suitable for pregnant patients? A comparison of nine different systems

Abstract: Background: Acute appendicitis is the most common non-gynecological emergency during pregnancy. The diagnosis of appendicitis during pregnancy is challenging due to changes in both physiological and laboratory variables. Guidelines suggest patients with suspected acute appendicitis should be stratified based on clinical scoring systems, to optimize the use of diagnostic imaging and prevent unnecessary surgery. Surgeons require additional information beyond that provided by imaging studies before deciding upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
10
1
5
Order By: Relevance
“…As with Mantoglu in 2020, with a sensitivity and accuracy of around 84 per cent, a positive gender balance of 3.18 was achieved and a negative advantage of chance of 0.5. 23 is achieved. In our sample 218 patients (78.4 per cent) reported nausea or vomiting and 50 were absent (21.6 percent).…”
Section: Symptomsmentioning
confidence: 90%
“…As with Mantoglu in 2020, with a sensitivity and accuracy of around 84 per cent, a positive gender balance of 3.18 was achieved and a negative advantage of chance of 0.5. 23 is achieved. In our sample 218 patients (78.4 per cent) reported nausea or vomiting and 50 were absent (21.6 percent).…”
Section: Symptomsmentioning
confidence: 90%
“…Frountzas et al [ 17 ]'s meta-analysis comparing RIPASA and Alvarado reported higher accuracy for RIPASA score [area under the curve (AUC) 0.9431 vs 0.7944][ 17 ]. According to a retrospective study, including pregnant and non-pregnant female patients by Mantoglu et al [ 21 ], the RIPASA score was most helpful in pregnant patients (highest AUC at 0.806)[ 21 ]. In a trial involving 3878 patients, Andersson et al [ 5 ] noted the Appendicitis Inflammatory Response (AIR) score to have high sensitivity for complicated appendicitis[ 5 ].…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
“…Din punct de vedere imunologic, fătul poate fi considerat o alogrefă fiziologică deoarece prezintă antigeni paterni [15,35,36]. În timpul sarcinii, sistemul imun matern dezvoltă toleranță tranzitorie la antigenele fetale, menținându-și în același timp capacitatea de protecție împotriva agenților patogeni infecțioși.…”
Section: Introducereunclassified
“…Un alt studiu ce a inclus 79 de paciente gravide cu dureri abdominale,spitalizate în cadrul Spitalului Universitar Sakarya, Serdivan, Turcia, între perioada mai 2014 -mai 2019, a evaluat nouă scoruri pentru diagnosticarea AA și anume sistemele: Alvarado, Eskelinen, Ohmann, AIR, RIPASA, Tzanakis, Lintula, Fenyo Lindberg și Karaman [36]. Au fost colectate și analizate acuzele la prezentare, rezultatele examenului obiectiv, precum și datele de laborator (leucocitoza, neutrofilie, PCR), iar ratele apendectomiei negative au fost evaluate în funcție de rezultatul histopatologic.Și aici, RIPASA, a avut cel mai bun rezultat.…”
Section: Introducereunclassified
See 1 more Smart Citation